2021
DOI: 10.47836/pjst.30.1.01
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning to Detect and Classify the Purity Level of Luwak Coffee Green Beans

Abstract: Luwak coffee (palm civet coffee) is known as one of the most expensive coffee in the world. In order to lower production costs, Indonesian producers and retailers often mix high-priced Luwak coffee with regular coffee green beans. However, the absence of tools and methods to classify Luwak coffee counterfeiting makes the sensing method’s development urgent. The research aimed to detect and classify Luwak coffee green beans purity into the following purity categories, very low (0-25%), low (25-50%), medium (50-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The model with the highest validation accuracy was then tested for its performance using data testing. The data testing results were displayed using a confusion matrix [45] [46].…”
Section: Methodsmentioning
confidence: 99%
“…The model with the highest validation accuracy was then tested for its performance using data testing. The data testing results were displayed using a confusion matrix [45] [46].…”
Section: Methodsmentioning
confidence: 99%
“…Hendrawan et al [20] and colleagues suggested utilizing Deep Learning approaches to detect and categorize purity levels in luwak coffee green beans. The study sought to detect and classify the purity of Luwak coffee green beans into four categories: deficient (0-25%), low (25-50%), medium (50-75%), and high (75-100%).…”
Section: Related Workmentioning
confidence: 99%
“…Penambangan data dalam pembelajaran mesin memainkan peran besar dalam hal data eksperimen dan perhitungan kompleks untuk interpretasi [18] [19]. Penggabungan machine learning dalam pengembangan pengetahuan masa depan melalui interpretasi data otomatis dengan bantuan berbagai model seperti klasifikasi, regresi, pengelompokan, dan lainnya [20] [21].…”
Section: Pendahuluanunclassified